Tamil Localisation Process – A case study - Sarveswaran, K.; Gihan, G. (My University, 2009)
Localisation has become an active area in computer field and many organisations and individuals are localising software into their preferred languages. Different people use different localisation processes to do localisation. We cannot see much difference in the existing localisation processes. There can exist more than one localisation for a language. This difference may occur if localisers follow different glossaries and style guides. Many software are localised to Tamil language too. The aim of this paper is to describe a Tamil localisation process that is followed in Sri Lanka.